Analisis Variabel Du Pont System Pada BUMN Sektor Konstruksi Periode 2012 – 2021 - Aryani, Neni; Adhi, Triyogo Moelyo (JURNAL ADMINISTRASI KANTOR; Vol 11 No 2 (2023): Jurnal Administrasi Kantor (Desember 2023), 2023)
This study aims to determine the company's financial performance using the du pont system. This research is quantitative research with a descriptive verification type. Population in this study are state- owned construction sector listed on the In donesia Stock Exchange (IDX). The sample of this research is the company’s annual financial statements for the period 2012-2021 with an observation system of 40. This study uses secondary data obtained from annual financial reports accessed on the company's website for the period 2012–2018 and the IDX for the period 2019–2021. The data analysis used in this research is Du pont analysis for descriptive analysis and multiple linear regression to verify the data. The data were processed using SPSS 25 for Windows. The independent variables in this study are Net Profit Margin (NPM), Total Asset Turnover (TATO), and Equity Multiplier (EM). The dependent variable in this study is Return on Equity (ROE). The results showed that simultaneo usly NPM, TATO, and EM had a significant effect on ROE with the results of Fcount 555,113 > Ftable 2.87 and Sig value 0.000 < 0.05. The contribution of the three variables is 97.7%, which means that NPM, TATO, and EM can affect ROE by 97.7% while the remaining 2.3% is influenced by another variable. Based on descriptive analysis using du pont system, fluctuating changes in return on equity are caused by net profit margin rather than total asset turnover and equity multiplier.     Keywords: Du Pont System, Equity Multiplier (EM), Net Profit Margin (NPM), Return on Equity (ROE), Total Asset Turnover (TATO).